Conduction of (Na, Ce) doped Bi5Ti3FeO15 ceramics after different annealing processes. (1st April 2013) - Huang, Z; Guo, S B; Cai, Z Y; Li, Y C; Wang, G S; Dong, X L
<x xml:space="preserve">Abstract</x> Abstract Bi5−xNax/2Cex/2Ti3FeO15 (BNTF-100x, x = 0, 0·05, 0·10, 0·20, 0·30, 0·40 and 0·60) ceramics were prepared via solid state sintering process. With x increasing, the resistivity increases at first and then decreases. The lower the concentration of oxygen vacancies, caused by more (Na, Ce) dopant adding, the less the deep trap energies in the band gap for the activated electrons to be mobile. For the samples containing high concentration of oxygen vacancies, the conductivities are higher when they are annealed in the air and oxygen than that in the vacuum. On the contrary, for the samples containing low concentration of oxygen vacancies, the conductivities of the samples in different annealing conditions behave quite the same way. Most (Na, Ce) doped Bi5Ti3FeO15 ceramics exhibit intrinsic conduction at high temperatures with corresponding activation energies of 1·1-1·6 eV, while the extrinsic conduction has a close relationship with the concentration of oxygen vacancies and the activation ability of electrons.